Web-based expert system application for diagnosing stunting disease using the forward chaining method - Munti , Novi Yona Sidratul (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Expert system is a system that seeks to adopt human knowledge to computers so that computers can solve problems as experts usually do. The Expert System asks for facts that will show symptoms of a particular disease and can provide an explanation of the results of the consultations that have been carried out. In diagnosis, an expert faces a problem including the answers found in the form of uncertain answers. The limited presence of an expert makes it difficult for some people to take steps or actions when exposed to disease due to lack of knowledge. The presence of the Expert System is made to replace the existence of an expert who is indirectly in the community. This system is based on website technology and is built using the PHP Native programming language and uses MySQL database storage. With the waterfall methodology used in system development, the stages are more structured and clear. The expert system created can produce a process of diagnosing stunting and other malnutrition in humans by using the Forward Chaining method. So that users are able to obtain information about stunting and other malnutrition.